Curcumin Alleviates Neuropathic Pain by Inhibiting p300/CBP Histone Acetyltransferase Activity-Regulated Expression of BDNF and Cox-2 in a Rat Model - Zhu, Xiaoyan; Li, Qian; Chang, Ruimin; Yang, Dong; Song, Zongbing; Guo, Qulian; Huang, Changsheng (PLOS ONE, 2014)
The management of neuropathic pain is still a major challenge because of its unresponsiveness to most common treatments. Curcumin has been reported to play an active role in the treatment of various neurological disorders, such as neuropathic pain. Curcumin has long been recognized as a p300/CREB-binding protein (CBP) inhibitor of histone acetyltransferase (HAT) activity. However, this mechanism has never been investigated for the treatment of neuropathic pain with curcumin. The aim of the present study was to investigate the anti-nociceptive role of curcumin in the chronic constriction injury (CCI) rat model of neuropathic pain. Furthermore, with this model we investigated the effect of curcumin on P300/CBP HAT activity-regulated release of the pro-nociceptive molecules, brain-derived neurotrophic factor (BDNF) and cyclooxygenase-2 (Cox-2). Treatment with 40 and 60 mg/kg body weight curcumin for 7 consecutive days significantly attenuated CCI-induced thermal hyperalgesia and mechanical allodynia, whereas 20 mg/kg curcumin showed no significant analgesic effect. Chromatin immunoprecipitation analysis revealed that curcumin dose-dependently reduced the recruitment of p300/CBP and acetyl-Histone H3/acetyl-Histone H4 to the promoter of BDNF and Cox-2 genes. A similar dose-dependent decrease of BDNF and Cox-2 in the spinal cord was also observed after curcumin treatment. These results indicated that curcumin exerted a therapeutic role in neuropathic pain by down-regulating p300/CBP HAT activity-mediated gene expression of BDNF and Cox-2.